Pembuatan Aplikasi Pengenalan Makanan Tradisional Sumatera Utara dengan Menggunakan Teknologi Augmented Reality - Abel Gaudenzi; Harya Bima Dirgantara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to develop an application that can display information about traditional food from North Sumatra in 3 dimensions using Augmented Reality Technology. This built-in application is expected to increase knowledge and educate the public about what are the traditional foods originating from North Sumatra. This research built this application using the Interactive Multimedia System of Design and Development (IMSDD) method. In application creation, this research use the Unity3D and the Vuforia SDK. The result of this research is an application of information introduction of traditional food from North Sumatra. Application output is generated in APK format for Android devices. From the UX result, it shows of 100% percentage that stated this application helps people to gain their knowledge about traditional foods from North Sumatra.